VALIDASI DAN ANALISIS KADAR AKRILAMIDA PADA KOPI TUNGKAL DENGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) - Harmita Swandi; Armini Hadriyati; Mukhlis Sanuddin (EKOLOGIA, 2020)
Acrylamide is a chemical compound found in roasted coffe at temperature above 120⁰C. potential to couse cancer in humans. The coffee used by processed at home in the village of Betara sub-district, Tanjung Jabung Barat, Kuala Tungkal, Jambi. The purpose of this study is to compare acrylamide content traditional coffee powder with the high performance liquid chromatography method (HPLC). The phase of motion used acetonitril : phosphate acid (80:20 v/v), using C18 or oktadesil silica (ODS) with size 250 nm × 4,6 mm,injection volume 20 μl, detector genesys 10S UV-Vis at wavelength 203 nm. Acrylamide is ground coffee was identified at retention time (tR) ± 5,825 minute. This method is proven valid with linearity y = 20717x + 28752, correlation coefficient (r) = 0,998%, the limit of detection 0, 32109 ppm and the limit of quantitation 1,07031 ppm, orecision with 2%. Acrylamide levels in coffee powder 1 to 4 respectively are 72,065 μg/g sample (1), 66,922 μg/g sample (2), 60,215 μg/g sample (3), and 61,422 μg/g sample (4). The four coffee samples showed that the acrylamide levels of each sample exceeded the safe limit of consumption of acrylamide released by FDA is 2 μg/g.